ফিরে দেখা জীবন - হুদা, এটিএম শামসুল (ঢাকা : প্রথমা প্রকাশন, 2014)
Autobiographical reminiscences of A. T. M. Shamsul Huda, former Chief Election Commissioner of Bangladesh
Akbar Ali Khan Collections
Keywords: হুদা, এটিএম শামসুল; Election officials -- Bangladesh -- Biography; Biography; Bangladesh -- Biography -- Officials and employees, Retired